2014
DOI: 10.1515/hsz-2013-0271
|View full text |Cite
|
Sign up to set email alerts
|

Citrate – new functions for an old metabolite

Abstract: Abstract:Citrate is an important substrate in cellular energy metabolism. It is produced in the mitochondria and used in the Krebs cycle or released into cytoplasm through a specific mitochondrial carrier, CIC. In the cytosol, citrate and its derivatives, acetyl-CoA and oxaloacetate, are used in normal and pathological processes. Beyond the classical role as metabolic regulator, recent studies have highlighted that citrate is involved in inflammation, cancer, insulin secretion, histone acetylation, neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
192
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 96 publications
3
192
0
1
Order By: Relevance
“…Additional antihemostatic and anti-inflammatory activities of citrate may indirectly derive from its effects on blood cell components, including reduced activation of white blood cells and platelets (24)(25)(26)(27)(28)(29), and protective effects against endothelial-cell inflammation and dysfunction (30). Furthermore, citrate may be directly involved as a signal molecule in several cellular processes related to inflammation and balance of oxidative species (31). On this basis, citrate may behave as a true anti-inflammatory agent (10,18).…”
Section: Rca: Basic Principles and Citrate Metabolismmentioning
confidence: 99%
“…Additional antihemostatic and anti-inflammatory activities of citrate may indirectly derive from its effects on blood cell components, including reduced activation of white blood cells and platelets (24)(25)(26)(27)(28)(29), and protective effects against endothelial-cell inflammation and dysfunction (30). Furthermore, citrate may be directly involved as a signal molecule in several cellular processes related to inflammation and balance of oxidative species (31). On this basis, citrate may behave as a true anti-inflammatory agent (10,18).…”
Section: Rca: Basic Principles and Citrate Metabolismmentioning
confidence: 99%
“…Numerous studies have demonstrated that the use of glycolysis and the tricarboxylic acid (TCA) 2 cycle intermediates for biosynthesis is a key feature of altered metabolism in cancer cells (6,7). Among others, citrate, an intermediate metabolite located at the crossroads of glucose metabolism and energy production, is an important sensor of energy homeostasis (8).…”
mentioning
confidence: 99%
“…The citrate carrier catalyses the transport of citrate, a product of tricarboxylate (TCA) cycle, out of the mitochondrion in exchange for malate, a process that profoundly influences energy balance in the cells (Bisaccia et al, 1989Kaplan et al, 1993;Iacobazzi and Infantino, 2014;Kolukula et al, 2014). In the cytosol, citrate is cleaved by ATP-citrate lyase to oxaloacetate and acetylCoA.…”
Section: The Citrate Carrier Cic (Slc25a1)mentioning
confidence: 99%
“…The CIC is the most studied mitochondrial carrier in inflammation (Infantino et al, 2011bIacobazzi and Infantino, 2014;Palmieri et al, 2015). Transport of citrate via the CIC and citrate metabolism appear to be critical for the activation of macrophages (Infantino et al, 2011b;Iacobazzi and Infantino, 2014).…”
Section: The Citrate Carrier Cic (Slc25a1)mentioning
confidence: 99%
See 1 more Smart Citation